2021
DOI: 10.4103/jmas.jmas_97_20
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision versus four-port laparoscopic cholecystectomy in an ambulatory surgery setting

Abstract: Background: Single-incision laparoscopic cholecystectomy (SILC) can be done as a day-case procedure and may have advantages over conventional laparoscopic cholecystectomy (LC). We present the results of our study looking at post-operative pain and post-operative recovery time. Methods: This was a single-institution randomised double-blind controlled trial. Seventy-three patients with symptomatic cholelithiasis were randomized to SILC ( n = 37)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Twelve RCTs and 3 systematic reviews compared SILC with greater port number LC [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. Of the 6 RCTs comparing SILC against 4-LC ( Table 4 ), 4 concluded that SILC was associated with less postoperative pain [ 25 , 26 , 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve RCTs and 3 systematic reviews compared SILC with greater port number LC [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. Of the 6 RCTs comparing SILC against 4-LC ( Table 4 ), 4 concluded that SILC was associated with less postoperative pain [ 25 , 26 , 28 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although Subirana et al did not find a difference in operative time, they noted that surgeon-rated subjective difficulty was higher for SILC [ 29 ]. Sulu et al specifically sought to determine whether operative duration for SILC could be reduced by adding a sub-xiphoid port for gallbladder retraction and noticed that operative time was halved for 2-LC compared with regular SILC (35.0 ± 12.3 vs 79.1 ± 7.7 min, P < .05) [ 36 ] ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…When compared with multiport laparoscopic surgery, SILC shows better cosmetic outcomes, post-operative pain control, and patient satisfaction, as well as shorter hospital stays. [7][8][9] However, SILC is not widely performed because the narrow working space limits the movement of instruments and causes crowding between instruments. [10][11][12] In 2011, the da Vinci Single-Site Instrumentation and Accessories (Intuitive Surgical, Inc., Sunnyvale, CA, USA) system was developed to overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%